NOTES ON THE HISTORY OF THE IRRIGATION SYSTEM (ON THE EXAMPLE OF THE WORK OF YAHYA GHULOMOV “THE HISTORY OF IRRIGATION OF KHWAREZM”) (TAMADDUN NURI JURNALI, 2025)
The article describes the research of the first Uzbek archaeologist Yahya Gulomov on the history of irrigation, which is one of the main areas of his scientific activity. In particular, the scientific significance of studying the scientist’s work “History of Irrigation of Khorezm” is discussed. The article also provides the opinions of contemporaries about this work of Y. Gulomov.